Codici dell'anima: itinerari tra mistica, filosofia e poesia Con un'antologia di scritti al femminile - FIUME, VALENTINA (Biblioteca di Studi di Filologia Moderna, 2021)
Codici dell'anima: itinerari tra mistica, filosofia e poesia. Con un'antologia di testi al femminile investigates the rhetoric of 'vision' at a theoretical, literary and linguistic level: through the analysis of a corpus of important authors of the twentieth century - Campo, Guidacci, Virgillito, Zambrano and Weil - it traces the routes of a new resemantization of some symbols from the mystical tradition. After a theoretical reflection on the most significant aspects of philosophical and poetic itineraries, the volume philologically analyzes the fundamental aspects of this new alphabet of ecstasy to arrive at the construction of a repertoire of symbols, intended as a mapping of presences and recurrences, analyzed in their aspects of continuity, redesign and innovation with respect to the medieval and modern background.